2017
DOI: 10.1021/acs.oprd.6b00361
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Endocrine Disrupting Chemicals in Wastewater by Enzymatic Treatment with Fungal Laccases

Abstract: In this study the enzymatic degradation of hormones and endocrine disrupting compounds (EDCs) was investigated in artificial mixtures and in real wastewater by fungal laccases (Trametes versicolor, Myceliophthora thermophila). Several studies have already reported the successful enzymatic degradation of EDCs. However, with regards to a large-scale application, the influence of some factors such as enzyme immobilization and costs are often lacking. Furthermore, the majority of studies investigated the removal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 61 publications
1
44
0
Order By: Relevance
“…An alternative approach is to mitigate the amount of laccase required by immobilizing it on a carrier or by recovering it and recycling it within the treatment system. Immobilizing laccase onto a carrier can yield high removals (Chen, Stemple, Kumar, & Wei, ; Le et al., ) although immobilization can sometimes lower activity relative to free laccase (Becker et al., ). Recently, several systems are under development to recycle laccase within wastewater treatment systems (Arca‐Ramos, Eibes, Feijoo, Lema, & Moreira, ; Lloret et al., ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach is to mitigate the amount of laccase required by immobilizing it on a carrier or by recovering it and recycling it within the treatment system. Immobilizing laccase onto a carrier can yield high removals (Chen, Stemple, Kumar, & Wei, ; Le et al., ) although immobilization can sometimes lower activity relative to free laccase (Becker et al., ). Recently, several systems are under development to recycle laccase within wastewater treatment systems (Arca‐Ramos, Eibes, Feijoo, Lema, & Moreira, ; Lloret et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…No additional mediators were added to the reaction mix although, since a whole fungal culture was used, many natural mediators were likely present. Finally, Becker et al (2017) examined the removal of endocrine disrupting compounds from municipal wastewater using laccases immobilized on carriers. Removal of EDCs was efficient even at low enzyme concentrations although adsorption onto the immobilized carrier system was a significant removal mechanism; in contrast, direct addition of free laccase into batch reactors did not yield significant EDC removal.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that Phanerochaete chrysosporium, a major WRF, does not have laccase genes [104]. Trametes versicolor is a WRF frequently cited in the literature that was shown to be effective in the removal of different pharmaceuticals (Table 1) [46,47,[50][51][52][53][54][55][57][58][59][60][61][62]72].…”
Section: Mechanisms Of Removalmentioning
confidence: 99%
“…Becker et al [57] showed that the degradation of hormones by laccases is feasible even at very low enzyme concentrations, and that immobilized enzymes displayed better removal performance compared to the free enzyme. Indeed, enzyme immobilization provides a more suitable environment for enzymes and may result in an increasing enzyme stability concerning pH, temperature, and storage time.…”
Section: Factors That Influence the Degradation Capabilitymentioning
confidence: 99%
“…A possible application for immobilized enzymes is the elimination of hazardous trace substances from wastewater or drinking water [46,47]. The oxidoreductase laccase was immobilized on PEMA-functionalized BT and tested in an application in order to demonstrate an alternative possibility to reduce water pollution of anthropogenic contaminants.…”
Section: Prospect and Applicationsmentioning
confidence: 99%